Effects of fatty acid saturation degree on salt-soluble pork protein conformation and interfacial adsorption characteristics at the oil/water interface. (April 2021) - Han, Zongyuan; Xu, Shuaiqiang; Sun, Jingxin; Yue, Xiqing; Wu, Zhaoxia; Shao, Jun-Hua
Abstract: The aim of this study was to explore the effect of fatty acid saturation degree on the adsorption behavior of salt-soluble pork proteins at the oil/water interface and to reveal the mechanism between the conformational change of adsorbed proteins and the interfacial adsorption characteristics. Protein conformation, interfacial protein concentration (Γs), interfacial pressure, interfacial rheology and emulsion stability were measured in the oleic acid/linoleic acid/linolenic acid emulsions (OAE/LAE/LNAE). The results showed that the fluorescence intensity of the emulsions all decreased, which implied that tryptophan residues were exposed to the external polar environment and fatty acids influenced the polarity of micro-environment. α-Helix content in the emulsifying layer of OAE was significantly higher ( P < 0.05) while β-sheets and β-turns in the emulsifying layer of OAE were significantly lower ( P < 0.05) than those in the emulsifying layers of LAE and LNAE. As the saturation degree decreased, α-helices decreased, β-sheets and β-turns increased, and surface hydrophobicity decreased, implying that spatial conformational re-arrangement occurred and the number of exposed hydrophobic groups influenced the formation of interfacial protein film. In addition, the interfacial pressure of OAE/LAE/LNAE all increased as a function of adsorption time. Moreover, OAE and LAE had higher increasing adsorption rates and interfacial pressures during the initial step (0–3000 s) before interfacial pressures gradually reached the equilibrium, which indicated that low unsaturation degree facilitated the diffusion and adsorption of salt-soluble proteins. The elastic modulus (Ed ) of the OAE and LAE increased rapidly within 0–1200 s, and gradually decreased. The viscous modulus (Ev ) of the OAE and LAE increased. Fatty acids with low unsaturation degree could facilitate faster improvement of viscoelastic properties and the denser gel-like network structures, thus enhancing the emulsification stability. Graphical abstract: Image 1 Highlights: Low unsaturation facilitated amphiphilic conformation re-arrangement. Low unsaturation strengthened the emulsification localization and formed better interfacial films. Low unsaturation contributed to the diffusion and adsorption of salt-soluble proteins. The evolution of salt-soluble protein adsorption behavior at the O/W interface was revealed.